40 years World Heritage Convention : popularizing the protection of cultural and natural heritage - Albert, Marie-Theres; Ringbeck, Birgitta (Heritage studies (Berlin, Germany) ;, 2015)
Since the adoption of the World Heritage Convention in 1972, the notion that cultural and natural heritage need to be protected and properly utilized has gained popularity. Over time, however, such utilization concepts were less focused on ideas of sustainability and became increasingly influenced by commercial interests. This publication discusses these developments and suggests potential solutions in order to deal with such unintended trends.